Development of energy-saving technology maintaining the functioning of a drying plant as a part of the cogeneration system - Chaikovskaya, Eugene (Eastern-European Journal of Enterprise Technologies, 2016)
The technology of the drying plant functioning at the level of decision making for the production of pellet fuel was suggested. The use of the integrated system of the estimation of a change in the air moisture content in the drying chamber, obtained on the basis of the mathematical and logical simulation as a part of the cogenerating system, allows coordinating the temperature and aerodynamic drying modes of timber drying on the basis of a change in the rotation frequency of the electric motor of the air fan by measuring the air temperature at the inlet into the heat exchanger. For example, with the production of 5,8 thousand tons of wood pellets per year, it is possible to provide 860 apartments of the area of 120 m2 with the pellet fuel, which allows reducing the cost value of the electric energy and of the heat production by 20–30 % and obtaining savings of financial resources up to 40 % with the use of pellet fuel for heating and hot water supply on the condition of considering the frequency regulation of the electric motor of the air fan for the timber drying